PENGARUH RASIO KEUANGAN TERHADAP ANALISIS FUNDAMENTAL MODEL PRICE EARNING RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2008-2010) - , RYSA BIMANTARA; , Laurentius Suparwoto, Drs., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Investment is the commitment of fundsor other resources is done at the expense of current consumption, which aimsto gain a number of benefits in the future to improve the welfare and gain life in the future that is better than life today. Today not a few investors who like to invest in securities in the capital market. This is because bonds can provide a better rate of return than investment in real assets, though the risks are also greater than the investment in real assets. Besides securities have greater flexibilitywhen compared to real assets to a portfolio formed (to manage and reduce the level of risk with risk diversification). To be able to invest appropriately, in general, investors will look at the information in the financial statements of companies, especially in the information about the financial ratios that are considered as indicators of financial performance of the company, because it can affect the performance of the company's return, risk, and the price of the shares of the company in question (usually projected by the ratio ofmarket price earning ratio). The purpose of this study was to investigate the effect of financial ratios, such as the liquidity ratio (current ratio), the solvency ratio (debt to equity ratio), the ratio of activity (total asset turnover), and the ratio of profitability (return on equity) to market ratio ( price earning ratio) is generally investors use it as an approach to project the outlook for stock prices in the next period. The model used in this research isthe multiple linear regression models and types of data used are secondary data from any manufacturing companies listed on the Indonesia Stock Exchangefor three years ie 2008, 2009, 2010. Purposive sampling conducted random sampling. The sample used was 70 manufacturing companies. The results of this research showed that the ratio of liquidity (current ratio), the ratio of profitability (return on equity) has a significant negative effect on price earning ratio or in other words, contrary to the theory and hypotheses, and the solvency ratio (debt to equity ratio) has a negative effect but not significant the price earning ratio. While the activity ratio(total asset turnover) has a positive but not significant to the price earning ratio. This research can be used as a reference for investors in predicting the future company's stock price and assist investors in making decisions to invest in the stock market.